ENTERPRISE RESOURCE PLANNING SYSTEM (ERP) ON COMPANY ERAJAYA BEAUTY & WELLNESS - Agus Sulaksono; Hadir Hudiyanto; Haryono; Julius Nursyamsi (Asosiasi Dosen Muda Indonesia, 2026)
PT Erajaya Beauty & Wellness is a business vertical within the Erajaya Group operating in the beauty and health industry. EBW imports, distributes, and operates a retail network selling beauty and health products throughout Indonesia. PT Erajaya Beauty & Wellness requires strategic company information. This cannot be achieved without the support of an information system, which calculates daily estimates and calculations. This problem can be addressed by using an ERP system. The purpose of this research is to collect all invoice, purchase order, GRN, item, sales, sales return, and purchase return data from the company immediately during the initial transaction, store, process, and update it in real time. This ensures that employees can share information, and managers can obtain more comprehensive, accurate, and timely information to support decision-making. The research method used was interviews with the company and business process managers at PT Erajaya Beauty & Wellness. Based on observations, after using the accurate ERP system, PT Erajaya Beauty & Wellness can directly control and view the required data in real time, resulting in greater efficiency.